Energy conservation and environmental sustainability during grinding operation of Ti–6Al–4V alloys via eco-friendly oil/graphene nano additive and Minimum quantity lubrication. (October 2020) - Ibrahim, Ahmed Mohamed Mahmoud; Li, Wei; Xiao, Hang; Zeng, Zhixiong; Ren, Yinghui; Alsoufi, Mohammad S.
Abstract: Conventional cutting fluids cannot fit the principles of green manufacturing in terms of cost, energy-saving, environmental and health impacts. Therefore, it is planned to develop high-performance cutting fluids based on biodegradable, health-friendly nanofluids that exhibit sufficient lubrication and cooling properties. Palm oil-based nanofluid containing different percentages of graphene nanoplatelets (GNPs) were prepared and evaluated utilizing the Minimal quantity lubrication (MQL) mode. The cutting, tribological and microstructure tests revealed that GNPs with the content percentage of 0.1 wt% decreased the specific grinding energy by 91.78% compared to dry cutting. Furthermore, the palm oil/0.1 wt% GNPs based nanofluid could lessen the specific cutting energy by 80.25% compared to commercially high-performance Acculube LB2000 because of the sharp reduction in the friction coefficient. Graphical abstract: Image 1 Highlights: The proposed nanofluid saved the energy by 91.78% compared to dry cutting. The proposed nanofluid saved the specific energy by 80.25% compared to LB2000. Cutting force is decreased by the action of palm oil-GNPs/MQL lubrication strategy. The surface quality is improved by palm oil-GNPs/MQL lubrication strategy. The friction coefficient of the sliding tribo-pairs is reduced by the nanofluid.